Periodontal tissue engineering using an apatite/collagen scaffold obtained by a plasma‐ and precursor‐assisted biomimetic process. (16th November 2021) - Kanemoto, Yukimi; Miyaji, Hirofumi; Nishida, Erika; Miyata, Saori; Mayumi, Kayoko; Yoshino, Yuto; Kato, Akihito; Sugaya, Tsutomu; Akasaka, Tsukasa; Nathanael, Arputharaj Joseph; Santhakumar, Syama; Oyane, Ayako
Abstract: Background and objectives: In the treatment of severe periodontal destruction, there is a strong demand for advanced scaffolds that can regenerate periodontal tissues with adequate quality and quantity. Recently, we developed a plasma‐ and precursor‐assisted biomimetic process by which a porous collagen scaffold (CS) could be coated with low‐crystalline apatite. The apatite‐coated collagen scaffold (Ap‐CS) promotes cellular ingrowth within the scaffold compared to CS in rat subcutaneous tissue. In the present study, the osteogenic activity of Ap‐CS was characterized by cell culture and rat skull augmentation tests. In addition, the periodontal tissue reconstruction with Ap‐CS in a beagle dog was compared to that with CS. Methods: The plasma‐ and precursor‐assisted biomimetic process was applied to CS to obtain Ap‐CS with a low‐crystalline apatite coating. The effects of apatite coating on the scaffold characteristics (i.e., surface morphology, water absorption, Ca release, protein adsorption, and enzymatic degradation resistance) were assessed. Cyto‐compatibility and the osteogenic properties of Ap‐CS and CS were assessed in vitro using preosteoblastic MC3T3‐E1 cells. In addition, we performed in vivo studies to evaluate bone augmentation and periodontal tissue reconstruction with Ap‐CS and CS in a rat skull and canine furcation lesion, respectively. Results: As previously reported, the plasma‐ and precursor‐assisted biomimetic process generated a low‐crystalline apatite layer with a nanoporous structure that uniformly covered the Ap‐CS surface. Ap‐CS showed significantly higher water absorption, Ca release, lysozyme adsorption, and collagenase resistance than CS. Cell culture experiments revealed that Ap‐CS was superior to CS in promoting the osteoblastic differentiation of MC3T3‐E1 cells while suppressing their proliferation. Additionally, Ap‐CS significantly promoted (compared to CS) the augmentation of the rat skull bone and showed the potential to regenerate alveolar bone in a dog furcation defect. Conclusion: Ap‐CS fabricated by the plasma‐ and precursor‐assisted biomimetic process provided superior promotion of osteogenic differentiation and bone neoformation compared to CS.